2021
DOI: 10.1016/j.resglo.2021.100050
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of Covid-19 mortality on the economy of Nigeria

Abstract: Objectives This paper is aimed at modelling the effect of COVID-19 mortality per population (CMP), a proxy for COVID-19 on the Gross Domestics Product (GDP) per capita per COVID-19 cases (RGDPC), a proxy for the economic wellbeing of a nation. Methods Nine models divided into three groups (Gaussian polynomial, other non-linear, and Gamma generalized polynomial models) were fitted for RGDPC data on CMP, collected from 1st June to 31st December 2020. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…The data used here are daily data collected from World Health Organisation (WHO) from 1st June 2020 to 31st December 2020, spanning 214 datasets, used by Iluno et al. ( 2021 ). The independent variable is a measure of COVID-19, termed COVID-19 Mortality per 1 million persons in the population (CMP), while the dependent variable is the GDP per capita per COVID-19 laboratory-confirmed cases (RGDPC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used here are daily data collected from World Health Organisation (WHO) from 1st June 2020 to 31st December 2020, spanning 214 datasets, used by Iluno et al. ( 2021 ). The independent variable is a measure of COVID-19, termed COVID-19 Mortality per 1 million persons in the population (CMP), while the dependent variable is the GDP per capita per COVID-19 laboratory-confirmed cases (RGDPC).…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 factor is also an extra burden to the wellbeing of the people (Pak et al ( 2020 ); Iluno et al. ( 2021 )).…”
Section: Introductionmentioning
confidence: 99%
“…However, findings on the influence of economic performance on COVID-19 mortality rates were rather mixed. For example, in Nigeria, while Hassan et al [ 58 ] discovered that higher GDP was associated with higher mortality rates, Illuno et al [ 22 ] concluded that such a relationship was non-linear. They suggested that reducing the COVID-19 mortality might enhance the nation's economic well-being.…”
Section: Covid-19 Mortality Rate Urbanization and Economic Performanc...mentioning
confidence: 99%
“…This is because the number of mortalities is limited to non-negative integer values, positively skewed, and can have a zero count. Therefore, estimation with other regression techniques, such as ordinary least squares [ 11 , 16 , 21 , 22 ], generalized additive regression [ 10 ], and autoregressive integrated moving average model [ 17 ], are not appropriate to model this sort of data. Therefore, this study suggests using the negative binomial regression technique to address this problem and obtain a more accurate estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the private sector seems to be a dominant source of health care providers, however, a private health system in Nigeria has not been fully integrated into the national pandemic response due to some legal and regulatory restraint by the regulators of the health sector. 37 This is concerning the fact that in the wake of the COVID 19 Pandemic in Nigeria, the Nigerian government, according to its power under Sections 2, 3, and 4 of the Quarantine Act, made the COVID-19 Regulation 2020. The Nigerian government's efforts to contain the COVID-19 pandemic included, among other things, limiting or prohibiting movement in most Nigerian states.…”
Section: Legal Impediments For a Private Health Care Provider Caring ...mentioning
confidence: 99%